Loss of PTEN Facilitates Rosiglitazone-Mediated Enhancement of Platinum(IV) Complex LA-12-Induced Apoptosis in Colon Cancer Cells - Lauková, Jarmila; Kozubík, Alois; Hofmanová, Jiřina; Nekvindová, Jana; Sova, Petr; Moyer, Mary Pat; Ehrmann, Jiří; Hyršlová Vaculová, Alena (PloS one, 2015)
We demonstrated for the first time an outstanding ability of rosiglitazone to mediate a profound enhancement of LA-12-induced apoptosis associated with activation of mitochondrial pathway in human colon cancer cells. This effect was preferentially observed in the G1 cell cycle phase, independent on p53 and PPARγ proteins, and accompanied with significant changes of selected Bcl-2 family protein levels. Further stimulation of cooperative synergic cytotoxic action of rosiglitazone and LA-12 was demonstrated in the cells deficient for PTEN, where mitochondrial apoptotic pathway was more stimulated and G1-phase-associated dying was reinforced. Our results suggest that combined treatment with rosiglitazone and LA-12 might be promising anticancer strategy in colon-derived tumours regardless of their p53 status, and also favourable in those defective in PTEN function.
Keywords: energetický metabolismus; RNA interference; Mitochondria; PPAR gamma; protinádorové látky; Cell Line, Tumor; Cell Proliferation; PTEN Phosphohydrolase; thiazolidindiony; Amantadine; Organoplatinum Compounds; Rosiglitazone; nádorový supresorový protein p53; Drug Synergism; amantadin; rosiglitazon; synergismus léků; RNA, Small Interfering; PPAR gama; Thiazolidinediones; lidé; Energy Metabolism; G1 Phase Cell Cycle Checkpoints; Humans; malá interferující RNA; kontrolní body fáze G1 buněčného cyklu; Tumor Suppressor Protein p53; Cell Cycle; Colonic Neoplasms; apoptóza; HCT116 buňky; proliferace buněk; HCT116 Cells; nádory tračníku; membránový potenciál mitochondrií; buněčný cyklus; fosfohydroláza PTEN; nádorové buněčné linie; organoplatinové sloučeniny; RNA Interference; Membrane Potential, Mitochondrial; mitochondrie; Antineoplastic Agents; Apoptosis